Application of IoT-Based pH and TDS Sensors for Optimization of Hydroponic Vegetable Production at Blasta Hidroponik - -, Vauzia -; Yulkifli, Yulkifli; Fevria, Resti; Jarlis, Roni (Fakultas MIPA Universitas Negeri Padang, 2025)
The implementation of IoT-based technology in hydroponic cultivation has become increasingly important to optimize vegetable production and ensure food security. This community service activity aimed to implement pH and TDS (Total Dissolved Solids) sensors based on Internet of Things (IoT) technology at Blasta Hidroponik, Padang City. The method involved four stages: socialization, technology design, implementation assistance, and monitoring evaluation. The target partner was Blasta Hidroponik, a hydroponic business located on Jl. Sumatera No. 1 Ulak Karang, Padang City, with a cultivation area of ±200 m². The implemented system included pH sensors with 0-14 pH measurement range (±0.1 accuracy), TDS sensors with 0-9999 ppm range (±2% accuracy), ESP32 microcontroller for WiFi connectivity, and Android-based mobile application for real-time monitoring. Results showed significant improvements in productivity (44% increase), cultivation cycle acceleration (8%), resource efficiency (25% water savings, 30% nutrient reduction), and labor optimization (reduced monitoring time from 3 hours to 30 minutes daily). Knowledge transfer was successful with 78% improvement in partner's understanding through pre-test and post-test evaluation. The IoT-based monitoring system proved effective in maintaining parameter stability with pH fluctuation reduced from ±1.2 to ±0.3 units, supporting optimal nutrient absorption and plant growth consistency